Increasing Student Engagement With Text: Exploring Student-Centered Activities to Build Literacy Skills - Preston, Sarah (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
This article focuses on a current issue many ELA teachers face: Students’ lack of engagement with text. The central idea is to determine the best way to utilize class time to help students become active learners who participate in the classroom instead of passive learners who struggle to retain the content. Furthermore, this article stresses the need for all content teachers to regularly seek out and discover new and engaging learning activities that will help connect students to content-area texts. The three activities that are examined here aresustained silent reading (SSR), interactive notebooks, and literature circles, each of which has the potential to bridge student learning to help develop mastery in English language arts and beyond.